1991
DOI: 10.1103/physrevlett.66.1138
|View full text |Cite
|
Sign up to set email alerts
|

Non-Markovian dephasing of molecules in solution measured with three-pulse femtosecond photon echoes

Abstract: The electronic dephasing of large molecules in solution is investigated with three-pulse photon echoes generated by 6-fs optical pulses. The observed dephasing behavior, which is analyzed with a model based on a stochastic coupling of the molecules with their heat bath, is clearly shown to be non-Markovian. Moreover, the correlation function of the fluctuations asymptotically approaches an exponential with characteristic times varying from 20 to 80 fs, depending on the solvent environment.PACS numbers: 42.50.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(77 citation statements)
references
References 15 publications
(4 reference statements)
0
76
0
Order By: Relevance
“…6 are longer than ever measured before in a room temperature liquid. [20][21][22][23][24][25][26] The reason for this slow optical dephasing is the motional averaging of the exciton over the energetic perturbations, caused by the rapid motions of the molecules in the liquid. Unfortunately, we have no information of the optical dephasing of TDBC monomers to evaluate the averaging process quantitatively.…”
Section: ͑23͒mentioning
confidence: 99%
See 2 more Smart Citations
“…6 are longer than ever measured before in a room temperature liquid. [20][21][22][23][24][25][26] The reason for this slow optical dephasing is the motional averaging of the exciton over the energetic perturbations, caused by the rapid motions of the molecules in the liquid. Unfortunately, we have no information of the optical dephasing of TDBC monomers to evaluate the averaging process quantitatively.…”
Section: ͑23͒mentioning
confidence: 99%
“…We therefore have to conclude that the optical dynamics of the TDBC-aggregates in water has to be described in a non-Markovian way, just as was found for single molecules in liquids. 21,22 The absorption spectrum A͑ ͒ can be calculated by summing over the various transitions from the ground state to the one-exciton band, each broadened by the optical dynamics…”
Section: ͑16͒mentioning
confidence: 99%
See 1 more Smart Citation
“…1 In the past decade, molecular dynamics simulation studies and ultrafast experiments on dye solutions have unearthed the basic picture of the solvation process as well as the relevant time scales. [2][3][4][5][6][7][8][9][10] Important aspects of the early-time dynamics, however, remained questionable, because it was not clear how the intramolecular vibrational dynamics could be separated from the solvation dynamical process itself. 8,10 Recently it was shown that comparative studies on the same dye in different solvents can distinguish between the two processes.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Another sensitive probe of solvation dynamics is femtosecond ͑stimulated͒ photon echo. [10][11][12][13][14][15][16][17][18][19][20][21] The decay of this echo is used to obtain a nonlinear response function from which a solvation correlation function can be constructed. Although photon echo is a more indirect probe of solvation dynamics than time-gated fluorescence, its time resolution is superior because it is only set by the optical pulse length.…”
Section: Introductionmentioning
confidence: 99%